Exogenous brassinosteroids application in purple passion fruit plants grafted onto a sweet calabash passion fruit rootstock and under water stress (2024)
The purple passion fruit is a fruit species of great importance in high Andean areas, but it can be affected by water deficit conditions. The objective of this study was to determine the effect of the application of brassinosteroids on purple passion fruit grafted on Passiflora maliformis and under water deficit. The plants were subjected to different levels of irrigation (100%, 50% and 25% of the evaporated amount) and some were applied with brassinosteroid analogue (DI-31). The fresh and dry mass of the aerial part and the root, leaf area, height of the aerial part, electrolyte loss, relative chlorophyll content, stomatal conductance, and maximum PSII quantum efficiency (Fv/Fm) were determined. It was observed that water stress negatively affected the height, leaf area, and fresh and dry masses of the plants at 84 days after treatment (dat). On the other hand, the results indicate a positive effect of the brassinosteroids on the height, leaf area, and fresh and dry masses of the plants at the different levels of irrigation at 84 dat. An effect of water stress or the exogenous application of brassinosteroids on electrolyte loss was not detected, but these factors did affect Fv/Fm at 28 dat. These results are important for the formulation of integrated management plans for the cultivation of Passiflora edulis f. edulis Sims in a climate change scenario.